A stochastic dynamic pricing model for mass consumer products (2017)
Consumer goods companies decides prices for large variety of products, considering that they handle several brands and number presentations. These decisions may generate dilution, which affects sales of other portfolio products and future sales of the same product, causing a considerable loss in revenue. We propose a stochastic optimization model to quantify the impact of the potential dilution on sales and provide the optimal policy in order to maximize profit, focusing on sales through a retail channel. We tested our model on a case study in the industry, using data of a leader company of massive consumer market, and discussed the results obtained.